(untitled) (Perner’s Contacts, 2010)
This paper deals with vehicle routing problem – the corresponding models and methods are presented. The design of the whole distribution system can be decomposed into long term, medium term and short term decision-making problems. The heart of performed analysis is short term decision making – the vehicle routing problem itself. There were identified the most important variants of vehicle routing problems which need to be solved for the purposes of optimization of pick-up and delivery of small consignments.